A Preliminary Account and Review of the Simple Methods for determining the Operational Parameters of Fishing Gear, Underwater, with Notes on its Application - Pradhan, M J (Fishery Technology, 1965)
A Preliminary Account and Review of the Simple Methods for determining the Operational Parameters of Fishing Gear, Underwater, with Notes on its Application